2019
DOI: 10.1111/ter.12429
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a geothermal anomaly using apatite (U‐Th)/He thermochronology in the Têt fault damage zone, eastern Pyrenees, France

Abstract: (U‐Th)/He ages on apatite obtained in the vicinity of the Têt fault hydrothermal system show a large variability. In the inner damage zone adjacent to the fault core, where fluid flows are concentrated, AHe ages display a large scatter (3–41 Ma) and apatite ageing. Samples from the outer damage zone show young ages with less dispersion (0.9–21.1 Ma) and apatite rejuvenation. Outside the damage zone, ages are consistent with the regional exhumation history between 20 and 12 Ma. The important age dispersion foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(74 citation statements)
references
References 50 publications
14
57
1
Order By: Relevance
“…In this study, we propose an extended analysis of (U-Th)/He on apatite (AHe) thermochronometer (a LT thermochronometer sensitive for a range of temperature between 30 and 90 °C, Gautheron et al, 2009;Shuster and Farley, 2009), in association to Rare Earth Elements (REE) analysis of dated apatites, to track the effects of surface and hidden thermal systems along the Têt normal fault (Pyrenees). We showed in a preliminary work (Milesi et al, 2019) that the analysis of REE mobility can help to interpret AHe ages scattering and thus evidence hydrothermal imprints on measured ages. In this previous work, we focused on an area located in the vicinity of an active hot spring cluster along the dormant Têt fault in the eastern Pyrenees.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…In this study, we propose an extended analysis of (U-Th)/He on apatite (AHe) thermochronometer (a LT thermochronometer sensitive for a range of temperature between 30 and 90 °C, Gautheron et al, 2009;Shuster and Farley, 2009), in association to Rare Earth Elements (REE) analysis of dated apatites, to track the effects of surface and hidden thermal systems along the Têt normal fault (Pyrenees). We showed in a preliminary work (Milesi et al, 2019) that the analysis of REE mobility can help to interpret AHe ages scattering and thus evidence hydrothermal imprints on measured ages. In this previous work, we focused on an area located in the vicinity of an active hot spring cluster along the dormant Têt fault in the eastern Pyrenees.…”
Section: Introductionmentioning
confidence: 92%
“…Low temperature thermochronometers revealed that the Canigou massif was mainly exhumed, and rapidly cooled, between ~30-20 Ma in relation with the Têt fault normal activity (Fig. 2) (Maurel et al, 2008;Milesi et al, 2019). The Cenozoic exhumation of the Carança and Canigou Dashed lines correspond to 95% confidence interval.…”
Section: Cenozoic Têt Fault Activity and Related Exhumation Of The Eamentioning
confidence: 98%
See 3 more Smart Citations